Revenue Intensification Policy Implementation Restaurant Tax on Regional Revenue Agency City of Tidore Islands - Syafril Muhammad; Abdul Kadir Ali; Yususf Kamis (Peneliti.net, 2023)
The restaurant tax is one of the local taxes collected by the local government of the Tidore Islands City. The Tidore Islands City Regional Revenue Agency as an agency in increasing regional revenue receipts, one of which is from restaurant taxes based on the goals and objectives to be achieved each year, namely through the intensification of regional revenue sources in accordance with the duties of the department. The purpose of this study is to find out empirical butki about the Implementation of the Restaurant Tax Revenue Intensification policy in the Tidore Islands City Regional Revenue Agency. The data collection techniques carried out are observation, interviews and literature studies. The data analysis method used in this study is qualitative data. From the results of the research conducted, it shows that the implementation of the restaurant tax intensification policy at the Tidore Islands City Regional Revenue Agency has not been too optimal, this is evidenced by the fact that there are still restaurant owners who are in arrears in paying taxes and do not really understand the function of taxes due to lack of socialization from related agencies.